Occurrence, distribution, air-seawater exchange and atmospheric deposition of organophosphate esters (OPEs) from the Northwestern Pacific to the Arctic Ocean. (August 2020) - Na, Guangshui; Hou, Chao; Li, Ruijing; Shi, Yali; Gao, Hui; Jin, Shuaichen; Gao, Yunze; Jiao, Liping; Cai, Yaqi
Abstract: Eleven organophosphate esters (OPEs) in air and seawater were investigated from the Northwestern Pacific to the Arctic Ocean. The concentration of Σ11 OPEs in air and seawater ranged from 231.56 to 1884.25 pg/m 3 and from 8.47 to 143.45 ng/L, respectively. Halogenated OPEs dominated in both two media. The slight decreasing trend was observed for OPEs in gaseous air, no obvious trend for particle-bound OPEs and in seawater. The net air-seawater exchange flux ranged from −792.68 to 590.29 pg/m 2 /day. The dry deposition flux ranged from 16.4 to 185 ng/m 2 /day with high value observed at the Bering Strait (64.70 ng/m 2 /day). The relationship between temperature and OPEs particle-bound fractions suggests that temperature might be a driving factor of OPEs long-range atmospheric transport (LRAT). This research highlighted that OPEs are subject to LRAT from the Asian continent to the northwestern Pacific and Arctic Oceans and demonstrated the "sink" in polar regions of OPEs atmospheric transportation. Graphical abstract: Unlabelled Image Highlights: First reported gaseous OPEs from the Northwestern Pacific to the Arctic Ocean. Air-seawater exchange, atmospheric dry deposition were estimated. High deposition fluxes founded in the Bering Strait and high Arctic. New evidence about the "sink" in polar regions of OPEs was exhibited.